Trends of tourism development in Ukraine - Iryna Skril (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The article is devoted to the actual subject - features development of tourism in Ukraine. Tourism in Ukraine legally declared as a priority of national culture and economy. The promotion of Ukraine as a European state requires the development of tourism industry. The modern concept of leisure activities organization leads to increased demand for tourism in those regions, which have the cultural, social, household identity of the nation, local community. These areas are presented in the most regions of Ukraine. Due to the wealth of historical, cultural, recreational, social and economic resources Ukraine has all essential prerequisites for intensive tourism development.